Internal and external coordinated open innovation ecosystems: Concept building and applying to Shanghai Zizhu International Education Park - Haiyan Yan; Linlin Wang; Xinyue Yan; Qiongbo Zhai (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In an environment marked with phenomena such as globalization and creation, open innovation is critical for universities to cooperate with external resources and meet the requirements of the era. To investigate open innovation ecosystem of higher education, we use secondary data and interviews to analysis interactive model of Zizhu International Education Park from both internal and external perspectives. The analysis result suggests that the open innovation ecosystem could have positive effects on the development of higher education. It can contribute to deepening the integration of production, teaching, and research; improve the efficiency of scientific research transformation; and use this part of the income to supplement school funding. While the university-industry collaborative relationship could also be a limiting factor for it.
Keywords: 650; open innovation; ecosystem; higher education